THE ROLE OF JAWI TAFSIR IN SOCIO-CULTURAL TRANSFORMATION OF THE NUSANTARA ISLAM: A STUDY ON TARJUMĀN AL-MUSTAFĪD - D. I. Ansusa Putra; Zikwan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
Studies  on  Islam  in  Nusantara  are  primarily  related  to  Islam's transmission  to  Nusantara.  Meanwhile,  the  role  of  vernacularization (localizing)  of  Islamic  sciences  by  Nusantara  scholars  -  including attention  to  vernacularization  of  interpretive  science  -  gained  less attention. This paper employs the vernacular concept from A.H. Johns, discussing  the  role  of  Jawi  Tafsir  in  the  Islamization  of  Nusantara  in the  early  phases  of  both  the  formulation  of  Islamic  Nusantara  Islam and  the  socio-cultural  transformation  of  Nusantara.  The  conceptual frameworks  are  related  to  enculturation,  adoption,  and  cultural adaptation,  in  which  vernacularization  occurs  in  each  of  these processes.  Through  studies  on  the  Jawi's  vernacular  interpretation (Tarjumān  al-Mustafīd),  this  paper  argues  that  in  the  early  scientific formulation of the Nusantara Islam that transformed the socio-cultural Nusantara,  Tarjumān  al-Mustafīd  played  a  significant  role.  With another  Jawi  commentaries,  Tarjumān  al-Mustafīd  then  became  the Nusantara's Islamic identity and proof of Islam with the archipelago's character.